A study of thrombocytopenia in pregnancy - Modi, Komal; Chaudhari, Jaydeep; Vaja, Disha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Thrombocytopenia is defined as low platelet count and if it is present during pregnancy can jeopardize the maternal and fetal outcome. Thrombocytopenia occurs in 6-15% of pregnancies. Causes of thrombocytopenia include gestational, idiopathic thrombocytopenia, preeclampsia, HELLP, DIC, malignancy and marrow failure. Aim of this study was to find out the common causes of thrombocytopenia in this hospital and management being used. Methods: Data was collected form those women who came to the antenatal clinic (booked) and labour room (unbooked) in the department of obstetrics and gynecology, GMERS Medical College and Hospital, Sola, Ahmedabad. Data of a total of 75 pregnant women were collected during the period of July 2018 to June 2019. Results: There were 66.67% cases of gestational thrombocytopenia, 13.33% related to preeclampsia, 8% in Eclamptic patients, 2.67% in HELLP and DIC, 6.67 in ITP, and lastly 2.67% in dengue cases. There were number of associated complication whether directly related (PPH) or part of the disorder. PPH was observed in 22.67% which is maximum among all complications. Other complications were part of major associated illness i.e. liver failure (6.67%), renal failure (5.3%), DIC (5.3%) and HELLP (8%). Conclusions: Mode of delivery was not influenced by platelet count, but for obstetric indications. Management of patients was as per the diagnosis. Single donor plasma is preferable to random donor plasma. PPH was the commonest complication and we should be wary of that.